1986
DOI: 10.3382/ps.0650114
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dietary Levels of Calcium and Phosphorus on Performance and Retention of These Nutrients by Laying Hens

Abstract: The first experiment utilized three levels of calcium (3.5, 4.5, and 5.5%) and three levels of available phosphorus (.24, .44, and .64%). The birds were 56 weeks old at the beginning of the experiment and were fed the experimental diets for 16 weeks. Egg production, egg weight, feed consumption, plasma calcium and phosphorus, egg shell quality, and tibia ash were not significantly affected by different dietary levels of calcium. Dietary levels of phosphorus did not have a significant effect on the aforemention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0
7

Year Published

1990
1990
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 19 publications
2
9
0
7
Order By: Relevance
“…However, basing on the results of many experiments, Roland (1986) considers that the intake of P by hens should be higher, reaching about 700 mg/hen/day at the peak of laying and between 500 and 600 mg later on. This assumption seems to confirm the results obtained by Keshavarz (1986) who found that, depending on P intake from the diet (540 -880 mg), the utilization of P ranged from 21.1 to 30.5%. According to Usayran and Balnave (1995), with daily intake of P between 352 and 837 mg, the utilization of this element ranged from 19 to 29% and was therefore similar to that observed by Keshavarz (1986).…”
Section: Phosphorus Balancesupporting
confidence: 80%
“…However, basing on the results of many experiments, Roland (1986) considers that the intake of P by hens should be higher, reaching about 700 mg/hen/day at the peak of laying and between 500 and 600 mg later on. This assumption seems to confirm the results obtained by Keshavarz (1986) who found that, depending on P intake from the diet (540 -880 mg), the utilization of P ranged from 21.1 to 30.5%. According to Usayran and Balnave (1995), with daily intake of P between 352 and 837 mg, the utilization of this element ranged from 19 to 29% and was therefore similar to that observed by Keshavarz (1986).…”
Section: Phosphorus Balancesupporting
confidence: 80%
“…Nesse caso, as galinhas absorveram 30% do conteúdo intestinal e 43% do cálcio das 20 às 24 h. Durante as próximas 4 horas, a absorção foi de 11% 1395 FARIA et al para o conteúdo intestinal e 15% para o cálcio. Os resultados indicaram que o sistema digestório da galinha tem menos cálcio disponível no período compreendido entre 4 e 6 h em comparação ao de 20 h. KESHAVARZ (1986) conduziu três experimentos com a finalidade de avaliar o efeito de altos níveis de cálcio em combinação com diferentes níveis de fósforo sobre o desempenho e a retenção dos referidos nutrientes pelas poedeiras. No experimento em que o balanço de cálcio e fósforo foi realizado, os níveis de cálcio foram de 3,5; 4,5; e 5,5% e os de fósforo disponível, de 0,24; 0,44; e 0,64% da dieta.…”
Section: Introductionunclassified
“…Este nível de ingestão de cálcio ficou pouco acima daquele preconizado por ZOLLITSCH et al (1996). No entanto, esses achados não indicaram possível efeito benéfico na retenção dos elementos cálcio e fósforo, embora alguns trabalhos evidenciam tal hipótese, quando o alimento é fornecido no período da tarde (ROLAND et al, 1973) ou contém níveis mais elevados de cálcio (KESHAVARZ, 1986).…”
unclassified
“…Leeson et al (1986), trabalhando com aves na fase de pré-postura, alimentadas com baixo teor de cálcio na ração, observaram que as aves tiveram sua produção de ovos prejudicada, quando o período de alimentação com dietas deficientes na fase de crescimento foi longo. No entanto, esta redução da produção voltou ao normal no momento em que a reserva óssea de cálcio foi restabelecida.…”
Section: Resultsunclassified
“…Entretanto, Cheng et al (1991) relatam que regime alimentar não afeta a taxa de maturidade de frangas. Leeson et al (1986) relatam que uma alimentação prolongada, com ração de crescimento, geralmente é utilizada para melhorar a eficiência de uso do cálcio. Desse modo, quando uma ração com alto nível de cálcio é introduzida, eventualmente maior quantidade é absorvida e temporariamente retida.…”
Section: Introductionunclassified